(untitled) (Research, Society and Development, 2022)
Introduction: The Brazilian population undergoes intense aging and a consequent increase in multimorbidity, impacting health services. In 2011, the Ministry of Health created the “Best at Home” program with the aim of promoting home care as a possibility to expand hospital beds at the client’s home and thus humanize care and reduce costs. Objectives: To analyze home hospitalizations of the Unified Health System (SUS) in the period 2008-2019 and correlate with hospitalization cost, clinical and epidemiological variables. Method: Quantitative study based on data from the Hospitalization System of the Unified Health System (SIH/SUS) from 2008 to 2019, available on the electronic platform of the Department of Informatics of the SUS (DATASUS). For trend analysis, the Mann-Kendall test was used and for analysis of the intervention effect, ARIMA models were adjusted, considering data from 2008-2011 without intervention and from 2012-2019 with intervention. Results: There was an increasing trend in the number of home admissions from 2008 to 2019 (=0.152 and p=0.537), as well as in the average cost per hospitalization (=0.061 and p=0.837) and for females over males (=0.606 and p=0.007). There was a downward trend in the average number of days per hospital stay (= -0.576 and p=0.011) and in the mortality rate (=0.212 and p=0.373). Conclusion: with a cost of less than 10% of the daily value of a hospital stay, home care reduces mortality and average days of hospitalization. Therefore, with population aging, home care programs such as “Best at Home” become fundamental.